May his memory not be lost: Inca Garcilaso in the Miguel de Cervantes Virtual Library (Revista de Crítica Literaria Latinoamericana, 2017)
This paper dscribes the website dedicated to Inca Garcilaso within the virtual library "Miguel de Cervantes". We will review its contents, materials and tools available for teaching of and research on the topic of this author, and present the results of its diffusion over the last three years.
Keywords: digitalization; Inca Garcilaso; Miguel de Cervantes Virtual Library; dissemination